Fronto-striatal glutamatergic compounds in compulsive and impulsive syndromes: A review of magnetic resonance spectroscopy studies. (May 2015) - Naaijen, Jilly; Lythgoe, David J.; Amiri, Houshang; Buitelaar, Jan K.; Glennon, Jeffrey C.
Highlights: Compulsivity and impulsivity are cross-disorder traits present in ASD, ADHD and OCD. Fronto-striatal deficits are associated with glutamate-related changes. ADHD, OCD and ASD patients may have increased Glx levels in the striatum. Paediatric ADHD and ASD tend to have elevated Glx levels in the ACC. Adults with ADHD and ASD tend to have reduced Glx levels in the ACC. Abstract: Compulsivity and impulsivity are cross-disorder traits observed in autism spectrum disorders (ASD), attention deficit hyperactivity disorder (ADHD) and obsessive compulsive disorder (OCD). Aberrant fronto-striatal glutamatergic signalling is core to the understanding of compulsive and impulsive disorders. In this review, the glutamate (Glu) neurochemistry of fronto-striatal circuits in paediatric and adult ASD, ADHD and OCD, as described in 59 studies, is outlined from the perspective of proton magnetic resonance spectroscopy ( 1 H MRS). Despite the methodological inconsistencies between studies, two observations stand out that form possible hypotheses for future studies. Firstly, a possible increase in Glx (combination of Glu, glutamine and GABA) in the striatum across ADHD, OCD and ASD. Secondly, an increased Glx signal in the anterior cingulate cortex in paediatric ASD and ADHD but a lower Glx signal in adult ASD and ADHD. This suggests neurodevelopmental changes in fronto-striatal glutamatergic circuits across the lifespan. Future studies should incorporate more homogeneous samples, perform MRS at field strengths of at least 3 Tesla and provide much more precise and standardized information on methods to improve our understanding of fronto-striatal glutamatergic transmission in compulsive and impulsive syndromes.